Impact of different substrates for spawn production and production of milky mushroom (Calocybe indica) - AMIT KUMAR MAURYA; VINNY JOHN; RAKHI MURMU; SOBITA SIMON (International Journal of Pharma and Bio Sciences, 2019)
Milky mushroom (Calocybe indica) has become the third commercially grown mushroom in India after button and oyster mushrooms. This mushroom is gaining popularity due to its attractive robust, white sporocarps, long shelf life, sustainable yield, delicious taste, unique texture and cholesterol free foods with certain important medicinal properties including their antiviral effect. The varied production potential of different substrates is due to the variations in their physical properties and nutritional composition. C.indica is rich in protein, lipids, mineral, fibre, carbohydrate and is abundant with essential amino acids. In addition to this, it has most of the mineral salts required by human body such as potassium, sodium, phosphorus, iron and calcium. Due to its alkaline and higher fibre content, it is highly suitable for people with hyperacidity and constipation. Experiment was conducted in the Mahewa region, Prayagraj district of Uttar Pradesh. In this study, Locally available substrates wheat straw, paddy straw, pea straw, cotton waste, maize straw, sugarcane bagasse and wheat straw in combination with paddy straw were evaluated to find out the best suitable substrate for spawn production of C.indica. Amongst the various spawn substrates evaluated for spawn production, pearl millet grain was found to be the best spawn substrate for early spawn run. Six locally available substrates such as; wheat straw, paddy straw, pea straw, cotton waste, maize straw, sugarcane bagasse, wheat straw in combination with paddy straw were evaluated for growth and yield parameters for the cultivation of milky mushroom. The probable reason for this finding may be that paddy straw has high water holding capacity, porosity and bulk density. Paddy straw was found to be the best substrate for cultivation of milky mushroom.